2017
DOI: 10.1186/s40645-017-0153-6
|View full text |Cite
|
Sign up to set email alerts
|

A review on the numerical simulation of equatorial plasma bubbles toward scintillation evaluation and forecasting

Abstract: Equatorial plasma bubbles (EPBs) have been a longstanding and increasingly important subject because they cause severe scintillations in radio waves from Global Navigation Satellite System satellites. The phenomenon was found in the 1930s as irregular ionosonde observations and was termed equatorial spread F (ESF). ESF is interpreted as plasma density irregularities associated with EPBs that have nonlinearly evolved into the topside ionosphere. Numerical simulations have been powerful tools to study the fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 84 publications
1
52
0
Order By: Relevance
“…In the growth phase the perturbation electric field associated with the instability is expected to get modified. The growth time of RT plasma instability is nearly 10-60 min (Kelley et al, 1979;Yokoyama, 2017), which is of the same order as that of F-ESF durations reported here for the early phase. It is known that the ambient electric field is a key parameter that plays an important role in the initial linear growth of RT plasma instability (Kelley et al, 1981).…”
Section: Duration Of Active Phase Of Esfsupporting
confidence: 80%
“…In the growth phase the perturbation electric field associated with the instability is expected to get modified. The growth time of RT plasma instability is nearly 10-60 min (Kelley et al, 1979;Yokoyama, 2017), which is of the same order as that of F-ESF durations reported here for the early phase. It is known that the ambient electric field is a key parameter that plays an important role in the initial linear growth of RT plasma instability (Kelley et al, 1981).…”
Section: Duration Of Active Phase Of Esfsupporting
confidence: 80%
“…Recent results from high‐resolution physics‐based equatorial plasma bubble (EPB) simulations illustrate the structure characteristics. Figure , which is taken from Yokoyama (), shows a representative EPB structure that resulted from bottomside zonal perturbations applied 1 hr earlier. The structure development is mapped along magnetic field lines that terminate at low altitudes in opposite hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, physics-based predictions must have the ability to predict the occurrence of EPBs by simulating the background ionospheric conditions; particularly the daily changes in the upward plasma drift near sunset. The next challenge is to then numerically model the formation and small-scale structure(s) of the EPBs themselves (see review by Yokoyama, 2017). In achieving both of these challenges, an EPB prediction capability would be able to forecast the occurrence of EPBs, their spatial extent and their impact on radio waves.…”
Section: A41 Ionospheric Scintillation Predictionmentioning
confidence: 99%